WORLD EXPERIENCE IN STIMULATING THE DEVELOPMENT OF CLUSTERS IN THE ELECTRONIC INDUSTRY - M. V. Chekadanova (Модернизация, инновация, развитие, 2018)
Purpose: the article deals with innovative clusters as a form of priority organization of R & d and production in high-tech sectors of the economy, presents foreign experience of creating clusters in the electronic industry, the factors of their functioning efficiency. The main goal of the article lies in the study of world experience of fostering clusters in the electronics and the synthesis of the main techniques and methods applied in this fi eld.Methods: the article is based on the analysis and synthesis of international experience of state support for the innovative development of the electronic industry. The methods of theoretical, functional and structural analysis were used in its preparation.Results: currently, the main driver of the national economy of Russia are innovations, the key factor for the successful implementation of which is the state support for new forms of interaction between science and industry in the most dynamic sectors, including electronics. Based on the study of world experience in stimulating the development of clusters, the article presents possible approaches to the organization of this work in the electronic industry of the Russian Federation.Conclusions and Relevance: the analysis of foreign experience of state stimulation of development of clusters in high-tech industries, on the one hand, confirms the correctness of the measures that are implemented by Russia in the course of solving issues of territorial and sectoral organization of innovation, and on the other, points to areas that require additional attention and concrete actions. These include: programs and special conditions for attracting foreign companies and scientists to perform research and development in Russia; a variety of tax and non-tax incentives for innovation; supporting government participation in the capital of startups and others.